Low-friction study between diamond-like carbon coating and Ti6Al4V under fretting conditions. (July 2019) - Ding, H.H.; Fridrici, V.; Geringer, J.; Fontaine, J.; Kapsa, Ph
Abstract: Low friction between DLC coating and Ti6Al4V alloy was investigated under fretting conditions on a fretting-wear testing machine. The results indicated that, during the beginning period, the Ti6Al4V surface was damaged as a consequence of adhesion (and abrasion), leading to high friction coefficients of around 0.5. With the test ongoing, a tribofilm was formed on the rubbed Ti6Al4V surface. This tribofilm was derived from the wear product of Ti6Al4V alloy with oxidization. Its nano-hardness and reduced elastic modulus were greater than the Ti6Al4V matrix. Meanwhile, structural transformation occurred on the rubbed DLC surface. The tribofilm and transformed carbonaceous layer prevented the Ti6Al4V alloy and the DLC surface from direct contact and led to low friction coefficients (below 0.2). Highlights: Friction of DLC coating/Ti6Al4V contact declined from 0.5 to 0.2 during running-in. Evolution of DLC coating and Ti6Al4V rubbed surfaces was investigated. Tribofilm and carbonaceous layer formed on Ti6Al4V surface led to low friction. The rougher surface led to more severe damage to Ti6Al4V and the coating.